Risk factors for sessile serrated lesions among Chinese patients undergoing colonoscopy - Zhang, Ru (2023)
Background and Aim: Serrated polyps have been recognized as a premalignant lesion accounting for a significant proportion of colorectal cancer. Limited data are available regarding the risk factors for colorectal sessile serrated lesions (SSLs). We aimed to investigate clinical risk factors of SSLs and compared them with colorectal adenomas in a study population of Chinese individuals. Methods: A retrospective case–control study was performed in an academic tertiary-referral center in Hong Kong. Subjects with SSLs and adenomas were identified from the hospital pathology database from January 2010 to December 2020, and additional clinical data were retrieved from the electronic patient record system. We compared clinical features and risk factors of SSL patients with those without these lesions. Results: A total of 2295 subjects were included in the study, including 459 subjects with SSLs, 918 subjects with adenomas, and 918 subjects with normal colonoscopy. By multi-variable logistic regression, compared with normal subjects, patients with SSLs only were significantly more likely to have dyslipidemia (adjusted OR: 1.431, 95% CI 1.008–2.030) and diabetes mellitus (adjusted OR: 2.119, 95% CI 1.439–3.122). Conclusions: Dyslipidemia and diabetes were independent risk factors for SSLs. Our findings suggest these metabolic factors may be important for the risk of SSLs. The findings may improve our understanding of SSLs and shed light on patient selection for screening and risk stratification.